Maternal outcomes of rheumatic heart disease in pregnancy - L., Hema Priya; Bhandiwad, Ambarish; Desai, Nagaraj; Kondareddy, Triveni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preexisting cardiac disease is seen in 1-3% of pregnancies. In developing countries, sequelae of rheumatic fever often constitute the majority of women with heart disease; whereas in developed countries, it is the congenital heart diseases. The aim of this study was to examine the changing trends and mode of care of women with Rheumatic heart disease in pregnancy over a period of five years in a tertiary care centre. Methods: Patient records over five years were retrieved and maternal and perinatal outcomes were documented. The present study reports the outcomes of 72 women with rheumatic heart disease. Results: The prevalence of heart disease in pregnancy in our study was 1.72%. The prevalence was higher among the rural population, and in lower socio economic strata. 30% of patients were diagnosed during pregnancy. The risk of complications co - related with their functional status at the onset of pregnancy. The mode of termination of pregnancy and indications for LSCS did not vary. However, the risk of complications was greatest during labour and post-partum period. The mean birth weight was 2.7 kg, however, 30% of term neonates were of low birth weight (<2.5 kg). Conclusions: Rheumatic heart disease continues to be a major cause of cardiac disease complicating pregnancy. However, early diagnosis, appropriate management prior to pregnancy, and good functional status at the time of entering pregnancy allowed for a good maternal and neonatal outcome.